An Alginate Hybrid Sponge with High Thermal Stability: Its Flame Retardant Properties and Mechanism - Jiang, Yuhuan (Polymers (Basel), 2019)
The worldwide applications of polyurethane (PU) and polystyrene (PS) sponge materials have been causing massive non-renewable resource consumption and huge loss of property and life due to its high flammability. Finding a biodegradable and regenerative sponge material with desirable thermal and flame retardant properties remains challenging to date. In this study, bio-based, renewable calcium alginate hybrid sponge materials (CAS) with high thermal stability and flame retardancy were fabricated through a simple, eco-friendly, in situ, chemical-foaming process at room temperature, followed by a facile and economical post-cross-linking method to obtain the organic-inorganic (CaCO(3)) hybrid materials. The microstructure of CAS showed desirable porous networks with a porosity rate of 70.3%, indicating that a great amount of raw materials can be saved to achieve remarkable cost control. The sponge materials reached a limiting oxygen index (LOI) of 39, which was greatly improved compared with common sponge. Moreover, with only 5% calcium carbonate content, the initial thermal degradation temperature of CAS was increased by 70 °C (from 150 to 220 °C), compared to that of calcium alginate, which met the requirements of high-temperature resistant and nonflammable materials. The thermal degradation mechanism of CAS was supposed based on the experimental data. The combined results suggest promising prospects for the application of CAS in a range of fields and the sponge materials provide an alternative for the commonly used PU and PS sponge materials.